Duszpasterstwo wśród młodzieży w prowincjach Zakonu Braci Mniejszych w Polsce - Kukiełka, Samuel Artur (Studia Pastoralne, 2026)
In the five provinces of the Order of Friars Minor in Poland the Franciscan youth ministry is realized in different forms and according to various concepts arising from the historical conditions as well as from reading the signs of our times in the Church. Each of the provinces realizes its own project of pastoral activity among young people. This article presents short characteristics of the Franciscan youth groups gathering mainly young people attending high schools. After presentation of the groups, taking into account the selected conclusions and postulates that appear in the Order’s document of 2002 entitled “Directions of Ministry of Vocations. Come and See”, and referring to The Preparatory Document for the 15th Ordinary General Assembly of Synod of Bishops on “Youth, Faith and Vocational Discernment” the most important tasks and challenges these groups are facing have been described.